Jual Beli Online dengan Menggunakan Sistem Pembayaran Paylater Perspektif Hukum Ekonomi Syariah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the Paylater Payment System. The development of digital technology has driven changes in the transaction system, including the emergence of the Paylater payment method, which allows consumers to shop on credit without a card. This system offers convenience for users by providing flexible payment access. However, from the perspective of Islamic Economic Law, the Paylater mechanism needs to be further analyzed regarding its permissibility and conformity with Sharia principles, such as the prohibition of riba (usury), gharar (uncertainty), and maisir (gambling). This research aims to analyze the concept of buying and selling using the Paylater system in e-commerce and its alignment with Islamic Economic Law principles. The research method employed is a qualitative approach with literature review and analysis of fatwas and regulations applicable in Islam. The findings indicate that the Paylater system can be permissible in Islam if it adheres to clear contract principles, does not involve elements of riba, and ensures transparency in fees and penalties. Therefore, stricter regulations are necessary to ensure that the Paylater services implemented in Indonesia align with Islamic economic principles.